The Influence of Product Feature on Purchasing Decision to Elderly Dietary Supplement Products Consumers: An Empirical Testing the Mediator Variable of Perceived Value - Nurittamont, Wasutida; Huaykaew, Nanthaporn (NEU ACADEMIC AND RESEARCH JOURNAL, 2021)
The purpose of research to study the influence on product feature on purchasing decision to elderly dietary supplement product consumers and testing the mediator variable of perceived value. The questionnaire was used as a tool to collect data from 400 elderly persons in Phra Nakhon Sri Ayutthaya Province. Non-probability sampling as purposive sampling use for analyzing data by descriptive statistics include frequency, percentage, mean, and standard deviation and regression analysis by enter for a hypotheses tested. The study found that the product features, including quality, packaging, convenience, and benefit influence on purchasing decision to dietary supplement products of elderly consumers. The testing mediator variable indicates that perceived value as a partial mediator variable of the influence of product feature on purchasing decision toward dietary supplement product of elderly consumers. The results of the study used as a guide for entrepreneurs of dietary supplements product for elderly consumers and developing products to consumers need, building perceived value of products. Moreover, the increasing competitiveness in the supplement product market as well.